2008
DOI: 10.1021/bm701225a
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Highly Porous Scaffolds for Cartilage Regeneration

Abstract: This study presents a new innovative method where electrospinning is used to coat single microfibers with nanofibers. The nanofiber-coated microfibers can be formed into scaffolds with the combined benefits of tailored porosity for cellular infiltration and nanostructured surface morphology for cell growth. The nanofiber coating is obtained by using a grounded collector rotating around the microfiber, to establish an electrical field yet allow collection of nanofibers on the microfiber. A Teflon tube surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(139 citation statements)
references
References 31 publications
0
136
1
Order By: Relevance
“…In collector 3, the installed Teflon sheet on gap region also appeared to be unable to provide support. Teflon might resist fibre attachment and provide repulsion effect [29]. In contrast with collector 4, fibres from collector 1 might not undergo drawing and tension, thus providing a more elastic property.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In collector 3, the installed Teflon sheet on gap region also appeared to be unable to provide support. Teflon might resist fibre attachment and provide repulsion effect [29]. In contrast with collector 4, fibres from collector 1 might not undergo drawing and tension, thus providing a more elastic property.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The latter approach generates micron-sized inter-fiber spaces because pore size, in general, scales with fiber diameter. As a possible compromise to maintain the nanometer-diameter fibers and high surface area and micrometer-diameter fibers for sufficient pore-size for air/fluid diffusion, some researchers have explored forming composites of nanometer and micrometer fibers [57,58], electrospinning nanometer fibers onto micrometer fibers [59], and electrospinning nanometer fibers of two polymers, and then later removing the fibers from one of the polymers to increase the porosity [60].…”
Section: Porositymentioning
confidence: 99%
“…Because biodegradability is an essential material requirement in tissue engineering, numerous potentially biodegradable polymers including poly(α-hydroxy acids) and their copolymers [11], polyanhydrides [12], collagen [13], gelatin [14], chitosan [15], or silk [16] have been used to fabricate scaffolds for cell culture. Numerous studies have shown that different types of cells including osteoblasts [17], chondrocytes [18], fibroblasts [19], keratinocytes [20], or cardiomyocytes [21] are able to adhere and proliferate well when cultured on those electrospun scaffold materials.…”
Section: Introductionmentioning
confidence: 99%